Required Consultation or Provoking Confrontation? The Use of the Referendum in Peace Agreements. Issue 2 (3rd April 2019) - Balasco, Lauren Marie; Carrión, Julio F.
ABSTRACT: This article challenges the unreflexive use of post-agreement referendums during peace processes. Post-agreement referendums are too broad in scope and generate polarising dynamics that can reopen the wounds that they seek to heal. Their apparent simplicity usually masks an extensive set of policy choices that voters must decide upon in a high stakes vote. This complexity not only makes it difficult for voters to understand the issues at hand, but it also creates opportunities for confrontation rather than reconciliation. Moreover, when a significant modicum of peace has been achieved, after years of violent conflict, voters approach the referendum with different frames of mind than when violence is still prevalent. As a result, they become risk averse. As prospect theory would predict, when voters see themselves in the 'domain of gains', they tend to have a strong preference for the status quo, making approval of post-agreement referendums more difficult. The problem for democratic representation is compounded when legislatures step in to salvage the agreements in the face of voters' rejection. Using the cases of Guatemala and Colombia, we conclude that thoughtful, open, inclusive, and deliberative legislative action is better than referendums to ratify peace agreements.